2012
DOI: 10.1007/978-1-4614-5894-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-1-Containing Membrane Vesicles: Origins, Formation, and Utility

Abstract: The stem cell antigen prominin-1 (CD133) is associated with two major types (small and large) of extracellular membrane vesicles in addition to its selective concentration in various kinds of plasma membrane protrusion. During development of the mammalian central nervous system, differentiating neuroepithelial stem cells release these vesicles into the embryonic cerebrospinal fluid. In glioblastoma patients, an increase of such vesicles, particularly the smaller ones, have been also observed in cerebrospinal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Therefore, the induction of Prom1-dependent autophagy during aging may be an intrinsic defense mechanism, which enables the RPE to cope with increased oxidative burden, accumulation of ubiquitinated/nonubiquitinated protein aggregates, and phagocytic activity. Although Prom1 was initially described as a surface antigen in normal hematopoietic stem cells 3 and cancer stem cells, 56 recent studies have demonstrated the presence of Prom1 in normal adult tissues including the retina suggesting that Prom1 has diverse physiological functions beyond the known association with cancer stem cells. Several Prom1 isoforms are expressed in the retina, 52 but there is no Prominin-2 (Prom-2) expression in the eye, 57 which perhaps explains why a Prom1 mutation in the human gene causes retinal degeneration without causing other pathological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the induction of Prom1-dependent autophagy during aging may be an intrinsic defense mechanism, which enables the RPE to cope with increased oxidative burden, accumulation of ubiquitinated/nonubiquitinated protein aggregates, and phagocytic activity. Although Prom1 was initially described as a surface antigen in normal hematopoietic stem cells 3 and cancer stem cells, 56 recent studies have demonstrated the presence of Prom1 in normal adult tissues including the retina suggesting that Prom1 has diverse physiological functions beyond the known association with cancer stem cells. Several Prom1 isoforms are expressed in the retina, 52 but there is no Prominin-2 (Prom-2) expression in the eye, 57 which perhaps explains why a Prom1 mutation in the human gene causes retinal degeneration without causing other pathological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid profile in EV subsets depends on the cell type (2), membrane origin, and the activity of membrane lipid scramblases, flippases, or floppases. There are few studies on the lipid distribution in different membranes (including lipid rafts) of stem cells; nevertheless, the presence of certain membrane proteins that bind to specific lipids, such as lactadherin and annexins (which bind to phosphatidylserine) and prominins (which bind to cholesterol), has been reported on stem cell EVs (34) (Figure 2). This phenomenon may reflect a distinct lipid distribution in stem cell EVs compared to the average distribution in their originating stem cells or that of EVs from other cells.…”
Section: Ev Composition Diversity and Functionsmentioning
confidence: 99%
“…Interestingly, prominin-1 (CD133) and prominin-2, which associate with cholesterol, are highly enriched in stem cell membrane projections, cytonemes, cilia, and microvilli, as well as on EVs, although the mechanisms by which prominins contributes to stemness, sensing, differentiation, or other stem cell functions remain unclear (3436). Tetraspanins play particularly prominent roles in cytonemes and EVs by giving them curvature and strength and by regulating the spacing, distribution, trafficking, and fusion of membrane proteins and their interacting partners (37).…”
Section: Ev Composition Diversity and Functionsmentioning
confidence: 99%
“… Upon transfection of Chinese hamster ovary (CHO) cells, prominin‐1 is strongly enriched in filopodia . Furthermore, prominin‐1 is released into various body fluids in association with small membrane vesicles . They originate from the tips of microvilli and cilia, where prominin‐1 + budding structures were detected .…”
Section: Introductionmentioning
confidence: 99%